Effect of natural and commercially produced juices on colour stability of microhybrid and nanohybrid composites - Razieh Meshki; Marjan Rashidi (Nature Publishing Group, 2022)
Abstract Objective This study aims to evaluate the discoloration rate of two types of composites, microhybrid and nanohybrid, after exposure to natural and commercially-produced juices. Materials and methods In this experimental study, 90 disc-shaped specimens with a thickness of 2 mm and a diameter of 10 mm were taken from two composites, microhybrid P4 (Kerr-ITALY) and nanohybrid Filtek Z250XT (3M-ESPE-USA) (two groups of 45). Then, the samples of each group were divided into five subgroups of nine and were immersed for 10 days for 4 h in five solutions of commercially-produced orange juice, natural orange juice, commercially-produced pomegranate juice, natural pomegranate juice, and distilled water (control group). The colour of the samples was measured by a reflective spectrophotometer using the CLEl*a*b colour space at baseline and after discoloration. Result The independent t-test showed that the mean discoloration rate (∆E) of nanohybrid composite exposed to commercially-produced orange juice, natural pomegranate juice, and commercially-produced pomegranate juice was significantly higher than microhybrid composite (P < 0.01). In addition, the test found that the highest discoloration rate of the nanohybrid composite was related to the effect of commercially-produced orange juice (∆E = 13.03) and the highest discoloration rate of microhybrid composite was related to the effect of natural pomegranate juice (∆E = 4.79). Conclusion According to the results, it seems that microhybrid composites are more resistant to discoloration than nanohybrid composites. According to the results, consumption of dyed drinks, particularly natural pomegranate juice, commercially-produced orange juice, and commercially-produced pomegranate juice, is not recommended in the first few days after composite restoration.